The community of inquiry framework in contemporary education emerging research and opportunities - Semingson, Peggy 1973-; Smith, Pete 1961-; Anderson, Henry I. 1947- (IGI Global, 2018)
"This book contains a deeper examination of research on online learning using the Community of Inquiry (COI) framework integrated or overlaid with a big data approach...sprung from a series of conversations that took place amongst this book's authors across multiple collaborative projects" ...
Includes bibliographical references
Keywords: Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on; Web-based instruction; Internet in higher education